Rebound phenomenon of proton pump inhibitors therapy - Benedeto-Stojanov, Daniela; Koraćević, Goran; Stojanov, Dragan; Koraćević, Maja; Ignjatović, Nebojša (Acta medicae Medianae, 2021)
Proton pump inhibitors (PPIs) are the most potent drugs for suppressing gastic acid secterion. They are used in the treatment of acid-peptic disorders, including peptic ulcer disease, gastroesophageal reflux disease, Zollinger Ellison syndrome, in the eradication of Helicobacter pylori infection, and ulcer prophylaxis. In the pharmacotherapy of these disorders, they have significantly suppressed the use of H2 blockers, like other, older groups of antisecretory drugs. Long-term PPI therapy leads to moderate hypergastrinemia (increased gastrin secretion) in 20-25% of patients. This hypergastrinemia results in rebound acid hypersecretion (RAHS) in 30-40% patients, who abruptly discontinue PPI. Most patients who abruptly discontinue PPI have symptoms of dyspepsia and gastroesophageal reflux, most commonly heartburn and a burning sensation in the esophagus. Therefore, care should be taken to properly discontinue PPI and reduce the dose of the drug before complete discontinuation. A less effective acid blocker (H2 blocker) can be switched, since H2 receptor blockers cause less pronounced hypergastrinemia and hyperplasia of enterochromaffin-like cells (ECL cells) compared to PPI.